On the Initial‐Boundary Value Problem for the Linearized Boussinesq Equation. Issue 1 (15th September 2014) - Himonas, A. Alexandrou; Mantzavinos, Dionyssios
<x xml:space="preserve">Abstract</x> This work is concerned with the initial‐boundary value problem for the Boussinesq equation. By employing the unified transform method of Fokas, novel solution formulae for the linearized "good" Boussinesq equation on the half‐line with various initial and boundary conditions are obtained. Moreover, these solution formulae are numerically illustrated in the case of concrete data. Finally, Boussinesq's original physical derivation of the so‐called "bad" Boussinesq equation is provided.